3D fluoroscopy-based imaging in the cardiovascular catheterization laboratory: past, present and future. (February 2013) - Dattilo, Philip B; Chen, Shiuh-Yung James; Carroll, John D; Messenger, John C
The ability to perform catheter-based cardiac procedures has revolutionized cardiovascular care over the past several decades. Advances in 3D imaging techniques now allow the interventional cardiologist to visualize a 3D perspective of a variety of vascular and cardiac structures. This potentially allows not only for a better understanding of complex anatomy, but also acts as a tool to assist the operator in determining the proper size, orientation and placement of interventional devices used during percutaneous coronary intervention and structural heart disease interventions. This review details the development, evaluation, uses and potential future innovations relating to 3D imaging techniques and methods using C-arm based x-ray technology.